THE CONTEXT OF MARGINALISATION OF WOMEN IN THE FILM 'KARTINI' - Dwiyani, Ni Kadek; Raharja, I Gede Mugi; Negara, I Nengah Sudika (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
"Kartini" The Movie (2017) directed by Hanung Bramantyo can be considered as a work of appreciation for the struggle of women in Indonesia. Kartini as one of the Indonesian heroines who fought for women's rights in Indonesia is worthy of being called a symbol of the struggle against the marginalisation of women. The nature of a woman in the culture attached to Kartini as the daughter of noble descendants often exposes her to situations where the clash of culture and logic she has raises inner conflicts, which tends to make her considered a child who dares to break the rules in her family. Kartini's figure is not portrayed as a woman who is only silent when she is faced with a situation where her "rights" as a human being are never taken into account. However, the treatment of women that she felt at the time, made her moved to have her own strength to dare to voice what she wanted for her life and nature as a woman. The context of marginalisation that appears in the film "Kartini" is heavily influenced by cultural factors and mindsets that at that time were still very closed to providing equal space for women. Kartini's struggle in this film is depicted as having a very strong desire to fight for the marginalisation of women in that era through her intelligent thoughts. The life journey of the figure of "Kartini" in fighting for equal rights and dignity of Indonesian women is at least able to be heard to a wide audience, so that the film "Kartini" can function as a medium of education for women who are currently still experiencing injustice in the context of marginalisation, to be more courageous in fighting for the rights they should get.